PMO-046 Audit of a new pathway for enteral feeding head and neck radiotherapy patients. (28th May 2012) - Sharp, S; Sheth, C H; Baughan, C; Ramkumar, S; Walters, E
Abstract : Introduction: It is well recognised that Head and Neck Cancer (HNC) patients often "have problems with eating and drinking and a substantial proportion have to cope with tube feeding". 1 With no national pathway, many units use gastrostomy tubes however, clinical indication and timing of placement are debated. 2 Due to gastrostomy tube complications, our unit routinely uses nasogastric tubes (NGT). Using data from a previous audit our centre developed a pathway for enteral feeding (EF) HNC radiotherapy (RT) patients 3 . This pathway includes advice on enteral feeding in this patient group, specifically when and who to electively NG feed and guidance on selecting suitable patients for elective day-case NG placement. The pathway was launched in May 2011 and impact on length of stay (LOS) assessed. Methods: All patients with primary HNC treated with RT from 1st June to 30th September 2011 requiring EF were included in the audit. Details of anthropometry, day of RT NGT passed, LOS, number of NGT's required and nutrition related readmissions were collected. Results: 12 patients met the inclusion criteria; one was excluded from analysis as they were receiving long term gastrostomy feeding prior to RT. Details of the remaining 11 patients are detailed in Abstract PMO-046 table 1 . Admissions >24 h occurred in two patients. One patient initially refused an NGT, subsequently needing admission for nutritional complications and an NGT. The second patient had laryngeal cancer, a diagnosis that doesn't normally require EF; therefore NG feeding was commenced due to unexpected late onset nutritional problems. Despite this using the pathway reduced the average LOS further to only 3 days. 3 Conclusion: Using our enteral feeding pathway and a multidisciplinary approach, elective NGT feeding in HNC RT patients can be safely established using day-case facilities. It is a cost effective nutritional treatment with no significant complications identified. The pathway provides a clear, safe, efficient and effective approach to nutritional care in HNC RT patients. Competing interests: None declared. References: 1. National Institute for Clinical Excellence. Improving Outcomes for Head & Neck Cancer . London: National Institute for Clinical Excellence, 2004. 2. Nugent, et al. Enteral feeding methods for nutritional management in patients with head & neck cancers being treated with radiotherapy &/or chemotherapy. Cochrane Database Syst Rev 2010;17 :CD007904. 3. Walters, et al. Dietetic service improvement for patients with head & neck cancer receiving radiotherapy treatment. University Hospital Southampton, 2010. (Unpublished).